+0  
 
+1
105
1
avatar+259 

1)

2)

3)

4)

5)

 

thanks!

 Dec 14, 2018
 #1
avatar+98034 
+2

1. ( x + 2) ( - x^2 + 2x - 6)  =

 

-x^3  + 2x^2  - 6x  - 2x^2 + 4x  - 12  =

 

-x^3  - 2x - 12

 

2.                      

                           2x^2    +  4x   +    11

         x - 2         [ 2x^3   + 0x^2  +  3x   -  2 ] 

                           2x^3   -  4x^2

                           _________________________

                                         4x^2 +  3x

                                         4x^2 -  8x

                                       _____________________

                                                    11x  -  2

                                                    11x  - 22

                                                   ___________ 

                                                             20                                  second answer

 

 

 

3.  f(x) = 3^x - 1

 

y  = 3^x - 1

 

y + 1  =  3^x        take the log of both sides

 

log (y + 1) = log 3^x     and we can write

 

log ( y + 1) =  x * log 3        divide both sides by   log 3

 

log (y + 1) / log 3    =  x        "swap"  x and y

 

log(x + 1) / log 3  =  y      

 

By the change-of-base rule we can write the left side as

 

log 3 (x + 1)    =   the inverse     {   last answer  }

 

 

 

4.   arcsin [ -sqrt (2)  / 2]  =  - pi/4

 

5.  9i (2 + 3i)  =  18i + 27i^2  =    18i + 27(-1)  =  -27 + 18i

 

 

 

cool cool cool      

    

 Dec 14, 2018

33 Online Users

avatar
avatar
avatar
avatar
avatar